Evaluation of the Circle of Willis with CT Cerebral Angiography in Patients Suspected of Intracranial Aneurysm (Nepalese Journal of Radiology, 2025)
Introduction: Intracranial aneurysms are common, occurring in 3.6-6% of the general population, with 85% involving the Circle of Willis. Most aneurysms are asymptomatic, but subarachnoid hemorrhage (SAH) is often the first and potentially fatal presentation. While intra-arterial digital subtraction angiography (DSA) is the gold standard, CT cerebral angiography offers a useful, non-invasive alternative, potentially reducing the need for conventional angiography.Methods: This descriptive, cross-sectional study was conducted from 31st December 2023 to 30th December 2024 at a tertiary center. Ethical approval was taken from the Institutional Review Committee (Ref: 910/2023). Plain CT head was done in symptomatic patients, which is then followed by CT cerebral angiography in case of intracranial hemorrhage. A purposive sampling technique was used to include 100 patients. Data on demographics, clinical history, and imaging findings were analyzed.Results: A total of 100 high-risk patients were evaluated using contrast-enhanced CT angiography of the Circle of Willis. The mean age was 66.12 ± 5.77 years, with 56 females (56%) and 44 males (44%). Hypertension (61%) and smoking (51%) were the most common risk factors. Intracranial hemorrhage was most frequently found in the intraventricular region (30% of total cases). Aneurysms were detected in 89 cases, predominantly saccular (86 cases~96.6%), with the anterior communicating artery being the most affected site (23 cases~25.84%).Conclusions: CT cerebral angiography effectively detects intracranial aneurysms, with saccular aneurysms being the most common type and the anterior communicating artery being the most common location. It is the best modality of choice for patients before undergoing invasive neuro-intervention procedures like DSA.